Comparative Study of Zakat Funds Collection Through Manual Fundraising and Digital Fundraising in Indonesia - Humaidi Humaidi; Umar Umar; Muhammad Ruslan Abdullah; Khaerunnisa Khaerunnisa (ITB AAS INDONESIA Surakarta, 2022)
The potential of zakat fund collection in Indonesia reached Rp233.8 Trillion or 3% of Indonesia's GDP. However, the realization of the collection of zakat funds is only Rp. 8.2 trillion or 3.4% of the total zakat collection potential in Indonesia. The non-optimal realization of the collection of zakat funds is influenced by collecting zakat, namely manual fundraising and digital fundraising. This study aims to compare zakat collection methods through manual fundraising and digital fundraising. This study uses a mixed-method, a combination of quantitative and qualitative approaches. The type of data used in this study is secondary data sourced from the Indonesian National Baznas Report. Based on the results of the study using the Independent Sample T-Test, there was a significant difference between manual fundraising and digital fundraising with a significant value of 0.034 (Sig. (2-tailed)